2017
DOI: 10.1007/s10495-017-1366-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase regulates the chemosensitivity of breast cancer cells to cisplatin-induced apoptosis

Abstract: Fatty acid synthase (FASN) is a key enzyme in fat biosynthesis that is over-expressed in advanced breast cancer stages. Cisplatin (CDDP) is a platinum-based drug used in the treatment of certain types of this disease. Although it was shown that FASN inhibition induced apoptosis by enhancing the cytotoxicity of certain drugs in breast cancer, its role in regulating the chemosensitivity of different types of breast cancer cells to CDDP-induced apoptosis is not established yet. Therefore, two different breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Fatty acids are essential components of biofilm lipids, signaling molecules and constituents of energy metabolism pathways (30)(31)(32). Among them, palmitic acid serves a prominent role in the formation of long-chain fatty acids containing 16 carbon atoms (C16:0), and studies have reported excessive accumulation of palmitic acid in breast cancer cells (33)(34)(35). ELOVL6 is a key enzyme in intracellular lipid metabolism, and has previously been associated with metabolism in fatty liver and diabetes (36).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are essential components of biofilm lipids, signaling molecules and constituents of energy metabolism pathways (30)(31)(32). Among them, palmitic acid serves a prominent role in the formation of long-chain fatty acids containing 16 carbon atoms (C16:0), and studies have reported excessive accumulation of palmitic acid in breast cancer cells (33)(34)(35). ELOVL6 is a key enzyme in intracellular lipid metabolism, and has previously been associated with metabolism in fatty liver and diabetes (36).…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates that FASN plays an oncogenic role in cisplatin-induced apoptosis of TNBC cells. FASN suppression in TNBC can therefore enhance cisplatin-induced apoptosis to overcome chemoresistance (119). Intensified FAO is also a characteristic of chemoresistant TNBC tumor cells.…”
Section: Impact Of Metabolic Reprogramming On Tnbc Chemoresistancementioning
confidence: 99%
“…However, multiple mechanisms of cisplatin-resistance have been identified in TNBC cells ( 118 ). Despite the potential deleterious effects of oleic acid on TNBC cells, one study demonstrated a potential synergistic relationship between oleate and Cisplatin on inducing apoptosis in MDA-MB-231 cells ( 68 ). Treatment with oleate (50 μM) increased the number of cells undergoing apoptosis when used in combination with Cisplatin compared to cells treated with Cisplatin alone, which was attributed to oleic acid-dependent downregulation of fatty acid synthase (FASN).…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 99%